Enforcing L2 Learner Autonomy in Higher Education: The Top 50 Cited Articles - Lilia Raitskaya; Natalia Mekeko; Elena Golubovskaya (National Research University Higher School of Economics, 2021)
Learner autonomy as both a pre-condition of self-efficacy and higher achievements in learning and an essential learning outcome has been in the highlight in the higher education domain for many years. This review aims to single out the most influential publications (with 10 citations or more) on foreign language and L2 learner autonomy in tertiary education in the highly reputed journals indexed with the Scopus database, with the publication period limited to the last ten years (2011-2020). The key findings show that the top 50 cited articles on learner autonomy broadly cover conceptual development; self-efficacy and motivation within the learner autonomy concept; educational technologies and web-based activities in fostering learner autonomy; country-specific issues of learner autonomy as the prevailing directions of study in the field of learner autonomy.